2015
DOI: 10.1016/j.cnur.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age and Comorbidity on Cervical and Breast Cancer Literacy of African Americans, Latina, and Arab Women

Abstract: Background Appropriate and timely screening can significantly reduce breast and cervical cancer morbidity and mortality. Racial/ethnic minorities and immigrant populations have lower screening rates and delays in follow-up after abnormal tests. Purpose In this study, we examined the relationship between age, comorbidity, breast and cervical cancer literacy in a sample of African American, Latina, and Arab women (N=371) from Detroit, Michigan. Methods Age-adjusted Charlson Comorbidity Index (ACC) was used c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 95 publications
0
6
0
1
Order By: Relevance
“…This is because women who receive comorbidity-related care are more likely to receive regular mammography as a result of regular primary care visits. In contrast, another study 23 reported the lower timely mammography among women of different racial/ethnical groups who had comorbidity because they might receive underserved medical care.…”
Section: Discussionmentioning
confidence: 89%
“…This is because women who receive comorbidity-related care are more likely to receive regular mammography as a result of regular primary care visits. In contrast, another study 23 reported the lower timely mammography among women of different racial/ethnical groups who had comorbidity because they might receive underserved medical care.…”
Section: Discussionmentioning
confidence: 89%
“…The majority of Arab American women understood that the purpose of a Pap test is to detect cervical cancer cells early (Salman, 2012; Shah et al, 2008). Overall, Arab American women had an above-average cervical cancer literacy score using the C-CLAT in terms of their awareness, knowledge and screening, and prevention and control of cervical cancer (X̄ = 10, SD = 3), similar to Black and Latina women (Talley & Williams, 2015); however, only a small number of Arab American women were able to answer more than 75% of the 16 questions correctly (Williams, Talley, & Smith, 2014; Zambrana et al, 2015). …”
Section: Data Synthesismentioning
confidence: 98%
“…Whereas some studies suggest no association, others indicate that hypertension is related to the increased likelihood of mammography screening. [17][18][19][20] Notably, a recent study on the effect of cardiovascular disease on cancer screening recommendation found that women with hypertension were more likely to adhere to mammography screening guidelines, compared with those without hypertension. 20 It is likely that in seeking treatment to manage their hypertension, these women have regular interactions with their health care provider, which also increases their chances of receiving additional preventive care, including mammography.…”
Section: Discussionmentioning
confidence: 99%